Suprasellar Lipoma - P. P. De Kort (Journal of the Belgian Society of Radiology, 2015)
Background: A 48-year-old woman suffering from headaches for a longer period of time underwent a MRI scan. Based on the MRI findings, she was referred to our hospital for further analysis of a suprasellar lesion. In addition, we performed a non-contrast and a contrast-enhanced CT scan.